A educação física escolar e ginástica nas tecnologias da informação e da comunicação: análise e possibilidades - Andreolli, Marcelle [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Gymnastics in the school environment, currently, is far from being a content worked in all its aspects and possibilities. Studies show that deficiencies in the training of Physical Education teacher hinder the development of gymnastics in school as much as (or even more) the lack of materials and infrastructure. Coupled with the deficiencies in training, we can add to this problem the lack of teaching materials available for consultation this teacher. Currently, the internet and all available search range thereby became a place for teachers to teach as much support as content of promotional materials and knowledge with easy accessibility. Thus, the aim of this study is to search on Youtube, which is part of the Information and Communication Technologies (ICT), videos to disseminate content focused on gymnastics in Physical Education, as well as analyze the published content and finally create a means disclosure of this material, targeting public teachers. Therefore, this research, qualitative, will be developed through three steps: 1) Survey on Youtube materials on gymnastics in Physical Education; 2) descriptive qualitative analysis of the contents disseminated by these media; 3) Creating a Facebook page for disclosure of found materials. The main results show 24 videos collected, among which more than half are related to competitive gymnastics, and the only course of action that does n't appear in the results is the physiotherapy. We were able to classify most of the videos regarding the levels of education also, and the Middle School appeared more than the other levels. The videos collected in this research are amateurs, only three documents by non-personal channels (accounts) on Youtube, most are specific placement of Physical Education teachers

A ginástica dentro do ambiente escolar, atualmente, está distante de ser um conteúdo trabalhado em todas as suas vertentes e possibilidades. Estudos apontam que deficiências na formação do professor de Educação Física dificultam o desenvolvimento da ginástica na escola tanto quanto (ou até mais que) a falta de materiais e infraestrutura. Aliada à deficiência na formação, podemos incluir a esta problemática a falta de materiais didáticos disponíveis para consulta dos professores. Atualmente a internet e todas as possibilidades de busca disponíveis por esse meio tornou-se para os professores um local tanto de apoio, para ensinar conteúdos, quanto de divulgação de materiais e conhecimentos com fácil acessibilidade. Diante disso, o objetivo desse estudo é pesquisar no Youtube, vídeos que divulguem conteúdos voltados à ginástica na Educação Física escolar, analisar os conteúdos divulgados e criar um meio de divulgação desse material, tendo como público alvo os professores. Para tanto, essa pesquisa, de natureza qualitativa, será desenvolvida por meio de três etapas: 1) Levantamento no Youtube de materiais (vídeos) sobre a ginástica na Educação Física Escolar; 2) Análise qualitativa descritiva dos conteúdos divulgados por essa mídia; 3) Criação de uma página no Facebook para divulgação dos materiais encontrados. Os principais resultados apontam 24 vídeos coletados, dentre eles mais da metade são relacionados à ginástica competitiva, e o único campo de atuação que não aparece nos resultados é o fisioterápico. Conseguimos classificar a maioria dos vídeos com relação aos níveis de ensino também, sendo que o Ensino Fundamental II apareceu mais do que os outros níveis. Os vídeos coletados nesta pesquisa são amadores, apenas três deles documentos por ... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Ginástica; Educação física - Estudo e ensino; Redes sociais; Tecnologias de informação e comunicação